Effect of internet-delivered cognitive behavioral therapy on quality of life in patients with symptomatic atrial fibrillation. (14th October 2021) - Sarnholm, J; Skuladottir, H; Ruck, C; Axelsson, E; Bonnert, M; Bragesjo, M; Venkateshvaran, A; Olafsdottir, E; Pedersen, S; Ljotsson, B; Braunschweig, F
Abstract: Background: Many patients with atrial fibrillation (AF) experience severe or disabling symptoms and suffer from impaired quality of life (QoL). AF symptoms are often not sufficiently alleviated by current treatments. Symptom preoccupation (fear of AF episodes, hypervigilance towards cardiac symptoms, worry about complications, avoidance of physical and social activities) plays an important role in AF disability and can be targeted by cognitive behavioural therapy (CBT). This is the first randomized controlled trial (RCT) evaluating internet-delivered CBT in patients with AF. Methods: We randomized patients to 10 weeks of CBT or routine care with AF-education (EDU) only. Inclusion criteria were ECG documented paroxysmal AF (≥1 episode/month); AF-care according to ESC guidelines; symptoms ≥EHRA IIb. Exclusion criteria were recent or planned ablation and severe medical or psychiatric illness. CBT was delivered over the internet by clinical psychologists. Main components were exposure to cardiac-related physical sensations and reduction of AF-related avoidance behavior. Patients were evaluated at baseline, post-CBT and 3 months (3M) post-CBT. The primary endpoint was AF-specific QoL (AFEQT) at 3M. Secondary endpoints were symptom preoccupation (CAQ), symptom frequency (SCL), symptom severity (SCL), general QoL (WHODAS) and AF-specific healthcare (AFSS) (abbreviations: see table legend). AF burden was measured by 5-day continuous ECG recording. After 3M, patients in the EDU group were offered CBT. The CBT group was further evaluated at 6M and 12M. Results: 127 patients (age 65.4±8.3; 58% female; AF duration 5.6±6.1 years) were randomized to CBT (n=65) or EDU (n=62). CBT significantly improved AF-specific QoL. The AFEQT score was 62.5±16.7 at baseline and increased by 21.0 in the CBT group compared to 6.0 in the EDU group resulting in an 15.0 points improvement (95% CI: 10.1–19.8; P<.001). CBT also significantly improved the secondary outcomes (table). Results were sustained 12 months after treatment (AFEQT; figure). The results from ECG monitoring (AF burden) are currently being analyzed. Conclusion: Internet delivered CBT significantly improved AF-specific QoL in patients with symptomatic paroxysmal AF already receiving routine AF care. The magnitude of QoL improvement was comparable to that obtained in recent rhythm control trials and the effects were sustained over 12 months. AF-specific CBT delivered via the internet has the potential to improve the well-being of a large group of patients who do not sufficiently improve from current treatment methods. Our data support the integration of psychological evaluation and treatment in a multifactorial approach to AF management. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The study was supported by grants from theSwedish Research Council (2016-01379), RegionStockholm (ALF project).